Penentuan Waktu Sadap Getah Pantung (Dyera lowii) di Lahan Rawa Gambut - Wahyudi Wahyudi; Antonius Triyadi; Nursiah Nursiah (HUTAN TROPIKA, 2023)
Pantung tree (Dyera lowii) is a critically endangered species that grows in peat swamps. Pantung cultivation is not only for commercial purposes but also for species conservation, reforestation and rehabilitation of degraded peat swamp land. One of the benefits of the pantung plant is to use its sap as a material for making pencil erasers, rubber toys and others. This study aims to determine the tapping time of pantung plant sap based on its growth rate. Based on the results of this study, the growth in diameter and height of pantung plants can be described through polynomial equations, i.e: y = -3.825941 + 4.1244995x + (-0.140316)x2 and y = 3.562047 + 0.212857x + 0.72187x2 respectively: The time for tapping pantung plant sap in peat swamp land is when the plant has reached a diameter of 20 cm or has reached a height of 12 meters. Based on the polynomial equation, the tapping time for pantung plant sap is 8 years old, when the pantung plant reaches a diameter of 20.42 cm; or at the age of 10 years, when the plant reaches a height of 12.91 meters